The governance of scientific assessment in the context of the Intergovernmental Panel on Climate Change: lessons for international cooperation in science, technology and innovation - Yulia Yamineva (Deutsches Institut für Entwicklungspolitik (DIE), 2014)
The Intergovernmental Panel on Climate Change (IPCC) has been an example of an effective science-policy interface in international environmental affairs. For its efforts “to build up and disseminate greater knowledge about man-made climate change and to lay the foundations for the measures that are needed to counteract such change,” the Panel was awarded the Nobel Peace Prize in 2007. The discussion paper outlines the main characteristics of the IPCC's governance framework in relation to: institutional structure and decision-making; the assessment process; communication of assessment findings and outreach activities; the role of the IPCC in policymaking; as well as its role in capacity-building work. In doing so, it reflects the reforms made by the Panel between 2010 and 2012 in response to the external review of its processes and procedures called for after errors were found in the Fourth Assessment Report. The paper concludes with an overview of strengths and weaknesses of the IPCC model which may be useful for other multilateral research-related initiatives.
Keywords: 330; Regionale + globale + transnationale Governance; Klimawandel